2022
DOI: 10.12659/msm.935426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Oxidative Effects of Isorhamnetin for Protection Against Lung Injury in a Rat Model of Heatstroke in a Dry-Heat Environment

Abstract: Background Isorhamnetin is a natural flavonoid compound with anti-inflammatory and antioxidant properties. However, its roles in alleviating lung injury associated with heatstroke remain unclear. Therefore, this study aimed to evaluate the protective effects of different isorhamnetin doses on lung injury in heatstroke rat models exposed to a dry-heat environment. Material/Methods Fifty Sprague-Dawley rats were randomly divided into 5 groups: normal control (0.9% saline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Patients mainly present with acute lung injury (ALI), accompanied by pulmonary edema, pulmonary hemorrhage, pleural effusion, and exudation of inflammatory cells and cytokines (150,176,177). ALI was also found in mouse and rat models of heatstroke (21,99,158,(177)(178)(179)(180)(181)(182)(183). Rhabdomyolysis is more common in patients with EHS, and several possible mechanisms cause such phenomenon (3,166,(184)(185)(186)(187)(188)(189)(190)(191)(192)(193).…”
Section: Tissue Injury Responsesmentioning
confidence: 99%
“…Patients mainly present with acute lung injury (ALI), accompanied by pulmonary edema, pulmonary hemorrhage, pleural effusion, and exudation of inflammatory cells and cytokines (150,176,177). ALI was also found in mouse and rat models of heatstroke (21,99,158,(177)(178)(179)(180)(181)(182)(183). Rhabdomyolysis is more common in patients with EHS, and several possible mechanisms cause such phenomenon (3,166,(184)(185)(186)(187)(188)(189)(190)(191)(192)(193).…”
Section: Tissue Injury Responsesmentioning
confidence: 99%
“…This failure leads to a dangerous elevation in core body temperature (Tcore), surpassing 40.6 • C, which in turn can cause central nervous system dysfunction, manifesting as delirium, convulsions, and coma. As a severe condition resulting from internal thermal injury, heatstroke presents a significant life-threatening risk and is associated with a notably high mortality rate (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Isorhamnetin (IRh), extracted from various plants including Hippophae rhamnoides L., Ginkgo biloba L., and Tamarix ramosissima, is a flavonoid-based substance and a direct metabolite of quercetin in mammals [12]. Numerous investigations have shown that IRh has exceptional anticancer, antioxidant, cardiovascular, and cerebrovascular protective properties [12][13][14][15][16]. According to recent research, IRh has also shown anti-inflammatory and immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%